HUBUNGAN KARAKTERISTIK SOSIAL EKONOMI DENGAN PARTISIPASI PETANI DALAM GERAKAN PENERAPAN PENGELOLAAN TANAMAN TERPADU (GP-PTT) KEDELAI DI KECAMATAN KEDAWUNG KABUPATEN SRAGEN - Adwiyana, Sandra Kasaniva; WIbowo, Agung; Wijianto, Arip (Caraka Tani: Journal of Sustainable Agriculture, 2016)
This research aim to analyse social economy characteristics of farmers, to analyse farmers participation, and to analyse correlation between social economy characteristics of farmers with participation of farmers in GP-PTT Soybean Plants at Kedawung District, Sragen Regency. Basic methods for this research is explanatory. Research was conducted at Kedawung District in consideration of Kedawung District is a district in Sragen regency which take part in GP-PTT Soybean Plants activity with an area of 1,000 hectare. Data analysis which used is Rank Spearman correlation aim to find out the relation of Social Economy characteristic of farmers with farmers participation in the activity of GP-PTT Soybean Plants. The sampling method that applied in this research is proportional random sampling. Numbers of respondents researched in this research are 50 respondents. Analysis to find out level of significance used t test. The social economy characteristics of farmers in this research are age, formal education, non-formal education, income, farm size, and farming experience. Participations of farmers in this research are participations in planning, execution, monitoring and evaluation, as well as the utilization of the results. The results of this research shows that there is very significance correlation between non-formal education with level of participation in planning, monitoring, and evaluation. There is a very significance correlation between farming experience with level of participation in planning.